The Link between Homocysteine and Omega-3 Polyunsaturated Fatty Acid: Critical Appraisal and Future Directions - Gianluca Rizzo; Antonio Simone Laganà (Biomolecules, 2020)
Omega-3 polyunsaturated fatty acids and B vitamins are linked to metabolic and degenerative disorders, such as cardiovascular disease and cognitive decline. In the last two decades, the interplay between B vitamins and omega-3 polyunsaturated fatty acids gained increasing attention. Expression control on enzymes involved in the pathway of homocysteine by polyunsaturated fatty acids has been proposed. The methylation process seems crucial for the metabolism of polyunsaturated fatty acids and their distribution within the body. This review summarizes the available data in humans about the link between homocysteine and omega-3 polyunsaturated fatty acids, with a special focus on the meta-analyses of randomized clinical trials. Even if the paucity of available information about the topic does not allow for definitive conclusions, a synergic action between polyunsaturated fatty acids and B vitamins may play a key role in regulating several metabolic pathways. This element could explain a stronger action on homocysteine levels when omega-3 polyunsaturated fatty acids and B vitamins are supplemented simultaneously. To date, a robust rationale of intervention to prevent metabolic diseases is lacking and could be beneficial for individual health and healthcare policy.